Skincare shopping: cultural industry’s influence on Indonesian metrosexual body discipline - Putranto, Teguh Dwi (Jurnal Studi Komunikasi, 2024)
The research aims to discover the cultural industry’s power by looking at body discipline practices in online skincare shopping activity among metrosexuals. Using virtual ethnography, we focus on Instagram postings that focus on digital text as a medium for seeing the form of discipline of metrosexual men. Regarding the research informants, the researcher determined six informants. The characteristics of these informants in this study are male, living/residing in Jakarta, Bandung, and Surabaya. Males interested in facial skincare products often. purchase through online shopping (repetition buying). Informants were obtained through a search using the keyword ‘metrosexual’ in the Instagram search field by and examined profiles that contain some information. Search results are sorted only among Indonesian metrosexuals. Data analysis began with observation of the informant’s Instagram account profile from the Text/Photo/Video/Comment that can be accessed publicly. Followed by interviews to explore the understanding of the meaning behind the practice of online shopping through Instagram posts. The results of this study show that by developing self-care expertise, the cultural industry and body discipline of metrosexual men through online skincare buying activities contribute to disciplining their bodies. Disciplinary power is applicable to metrosexual males who receive discipline from facial skincare product businesses as well as from guys who post about these products. According to Adorno’s research, social media is used as a disciplining tool by the cultural business for metrosexual guys, and this is perceived through the lens of the panopticon mechanism.